A house divided - Wells, Jonathan Daniel, 1969- author.
1 online resource.
Keywords: Consolidating one of the most complex and multi-faceted eras in American History, this new edition of Jonathan Wells's A House Divided unifies the broad and varied scholarship on the American Civil War. Amassing a variety of research, this accessible and readable text introduces readers to both the war and the Reconstruction period, and how Americans lived during this time of great upheaval in the country's history. Designed for a variety of subjects and teaching styles, this text not only looks at the Civil War from a historical perspective, but also analyzes its ramifications on the United States and American identities through the present day. This second edition has been updated throughout, incorporating new scholarship from recent studies on the Civil War era, and includes additional photographs and maps (now incorporated throughout the text), updated bibliographies, and a supplementary companion website.